Perancangan Knowledge Management System Obat Tradisional untuk Diabetes Mellitus - Evasaria Magdalena Sipayung; Cut Fiarni; Richard Aditya (Prosiding SISFOTEK, 2018)
Management of Type 2 Diabetes Mellitus requires multidisciplinary treatment that includes non-drug therapy and drug therapy. Drug related problems, the state of occurrence of a discrepancy in the achievement of the goal of therapy as a result of using drug. Therefore, drug therapy can use traditional medicine as alternative solutions because it has minimal side effects. But seen from the development of information circulating regarding traditional medicine DM-reviewed yet complete. And if the information required aspects are met then it will have a positive impact benefits in terms of medical, especially in the dissemination of information. In the midst of the development of information technology today, the role of the application can help to contribute to improve the situation is the case today. Problems that occur at this time are with the limited media collaborative applications that are in the process of delivering, distribution, and storage of existing knowledge, resulting in knowledge sharing process is inhibited. To solve these problems, this research designed a Knowledge Management System (KMS). KMS was developed with web-based technology Web.2.0. With KMS design, then the process of sharing knowledge is not only shared by every user but is collaborative with the doctor to ensure the dissemination of knowledge